SORAKDASTRA: Innovation in Learning Media to Enhance Basic Movement Skills of Blind Students - Praditya, Yunita Octa; Juniarisca, Dwi Lorry; Pradana, Febryansah Gilang Aris (Postgraduate, University of Mataram, 2024)
The purpose of this research is to improve the basic movement skills of blind students through the application of SORAKDASTRA media in circuit training. SORAKDASTRA utilizes circuit training, which is used to conduct basic movement exercises tailored to the types of basic movements in physical education learning. The research method employed is developmental. This development research uses the ADDIE model design (Analysis, Design, Development, Implementation, Evaluation). The data collection instrument is a questionnaire using media assessment instruments and basic movement skills instruments. Data analysis in this study was conducted using quantitative descriptive analysis. Data collection was carried out over one month and included six accompanying sessions. Subsequently, the basic movement tasks designed for the students were validated by experts and practitioners in physical education with scores of 98.6% for adaptive physical education experts, 97.3% for motor skills experts, 98.6% for blind experts, 94.6% for media experts, and 85.3% for surface design experts. SORAKDASTRA is a book made from scrap fabric and embroidered in 3D to create a raised effect on the images of basic activities. Based on statistical analysis, the results of the non-parametric test for skills were significant (Sig<0.05), indicating an improvement in the learning outcomes for non-locomotor, locomotor, and manipulative basic movement skills among students at SLB A. The learning outcomes for the students improved by 57% using the N-Gain test. Based on data analysis and discussion, it can be concluded that teachers and blind students greatly need the SORAKDASTRA learning media to enhance basic movement skills (non-locomotor, locomotor, and manipulative).